PENERAPAN NEW PUBLIC SERVICE DALAM PELAYANAN JASA WESEL POS PADA PT. POS BAGAN BATU KECAMATAN BAGAN SINEMBAH KABUPATEN ROKAN HILIR TAHUN 2014-2015 - Putri Nanda Ginting; Baskoro Wicaksono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Implementation of New Public Service in postal money order services at PT. Pos Bagan Bagan Batu subdistrict Sinembah Rokan Hilir Regency Year 2014-2015 is a new service that is implemented in Indonesia with the interests of citizens because it considers that the failure of New Public Management, the government preoccupied with the affairs of increased economic growth, increased productivity, treats its citizens as customers, the fulfillment of the public interest is released into the arena of market mechanisms. Therefore, the New Public Service restore essential government functions that prioritize the interests of its citizens. Formulation of the problem in this research is how the application of new public service at PT. Pos Bagan Batu Year 2014-2015 and how the quality of the implementation of new public service at PT. Pos Bagan Batu Year 2014-2015.The research was conducted at PT. Pos Bagan Bagan Batu subdistrict Sinembah Rokan Hilir, purpose of this study was to determine how the application of new public service at PT. Pos Bagan Batu 2014 and 2015 and the quality of implementation of new public service at PT. Pos Bagan Batu, type of research in this thesis is qualitative descriptive that is by collecting data and facts as well as information obtained from the field and then processed and analyzed further by existing theories.The results of field research on the informant and the data collected, the outline can be concluded that the application of the new public service in postal money order services at PT. Pos Bagan Bagan Batu subdistrict Sinembah Rokan Hilir not accomplished in accordance with the existing theory. This can be seen by the results of interviews and the data obtained during the research field.Keywords: New Public Service, Services, Wesel Pos